HUBUNGAN STATUS FISIK AMERICAN SOCIETY OF ANESTHESIOLOGIST DENGAN DERAJAT SHIVERING PADA PASIEN PASCA SPINAL ANESTESI DI RSUD GRATI KABUPATEN PASURUAN - Eko Imam Prasetyo; Nafolion Nur Rahmat; Iin Aini Isnawati (NHM PRESS, 2023)
One of the most frequent issues with spinal anesthesia is shivering, which is a repeated and involuntary muscular activity. One of the elements thought to contribute to the development of post-anesthesia shivering is Physical Status ASA. The aim of this study was to compare the Physical Status ASA (American Society of Anesthesiologists) score with the shivering scale in patients who had undergone post-spinal anesthesia at Grati Hospital in Pasuruan. This kind of study uses cross-sectional correlational methodology. Between August 1 and August 31, 2022, this study was done in Grati Hospital - Pasuruan Regency. 51 patients who had had post-spinal anesthesia were included in the study. 46 respondents who matched the inclusion and exclusion criteria were randomly selected at Grati Hospital - Pasuruan Regency. The research instrument used a medical record and an observation sheet. The statistical test used in this study was Somers'D with α = 0.05. The results of this study indicate that 24 respondents (52.17%) experienced shivering with the highest incidence on a scale of 2 (moderate Shivering) as many as 11 respondents (23.91%). Analysis Somers'D obtained a significance value of ρ value = 0,009 < α = 0,05. These results indicate that there is a significant Correlation between Physical Status ASA and shivering scale in post-spinal anesthesia patients at Grati Hospital, Pasuruan Regency. It is hoped that efforts to reduce Physical Status ASA can reduce the shivering scale in post-spinal anesthesia patients and this study can be a reference for improving the quality of services at Grati Hospital, Pasuruan